Ionospheric disturbance effect on NNSS satellite positionings at Syowa Station - Igarashi, Kiyoshi; Ogawa, Tadahiko; Maeno, Hideo; Kuratani, Yasukazu (National Institute of Polar Research, 1988)
P(論文) An experiment for investigating a relation between geomagnetic disturbance and satellite positioning error in the polar region was carried out at Syowa Station, Antarctica, in 1985 and 1986 with a two-wave (150 and 400MHz) NNSS receiver. From the analysis of positioning data of about 10000 passes over 245 days, it is clearly found that the position determination error increases with increasing geomagnetic disturbance level (local K-index) and the number of passes on which the position determination is succeeded decreases by one or two per day when K-index is large. These results suggest that when the ionosphere is highly disturbed the 150 and 400MHz radio waves from the satellites are strongly scattered by ionospheric irregularities and/or spatial gradients of the electron density associated with ionospheric disturbances. departmental bulletin paper